The Relationship Between Pregnant Women's Knowledge About Anemia and Stunting Incidents at the Panyabungan Jae Community Health Center, Panyabungan District, Mandailing Regency, Christmas 2022 - Rosiana, Agnes (Benih : Journal of Midwifery, 2023)
This study aims to delve deeper into the relationship between pregnant women's knowledge of anemia and the incidence of stunting among children at the Panyabungan Jae Community Health Center, located in the Panyabungan District, Mandailing Natal Regency, in 2022. Employing an analytical observational design, the research involved 200 pregnant women as research samples. Data were collected through structured interviews using a questionnaire focusing on pregnant women's knowledge about anemia, while children's nutritional status was assessed to determine the incidence of stunting. Statistical analysis included correlation and regression tests to examine the relationship between pregnant women's knowledge of anemia and the occurrence of stunting in their children. The study results revealed a significant correlation (p < 0.05) between the level of knowledge of pregnant women about anemia and the incidence of stunting in their offspring. Specifically, pregnant women with a better understanding of anemia tended to have children with a reduced risk of stunting. Furthermore, factors such as socioeconomic status, access to health services, and dietary habits were identified as potential influencers in the relationship between pregnant women's knowledge about anemia and stunting. These findings underscore the importance of educating pregnant women about anemia as a fundamental aspect of efforts to mitigate stunting in children. Additionally, enhancing health services at Community Health Centers and raising public awareness about the significance of optimal nutrition during pregnancy are essential strategies to address the issue of stunting in the region effectively.